2016
DOI: 10.1093/jisesa/iew095
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal ofAmblyseius swirskii(Acari: Phytoseiidae) on High-Tunnel Bell Peppers in Presence or Absence ofPolyphagotarsonemus latus(Acari: Tarsonemidae)

Abstract: Amblyseius swirskiiAthias-Henriot (Acari: Phytoseiidae) is a predatory mite used to control thrips (Thysanoptera), whiteflies (Bemisia tabaci Genn., Hemiptera: Aleyrodidae), and broad mites (BMs) (Polyphagotarsonemus latus Banks, Acari: Tarsonemidae). Dispersal of A. swirskii, using the ornamental pepper “Explosive Ember” as a banker plant was evaluated for control of BMs in high-tunnel peppers. Open-canopy plants (5 weeks old) versus closed-canopy plants (10-weeks old) were used to evaluate the effect of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Low numbers of A. swirskii may also be explained by their high dispersal capacity. Amblyseius swirskii are highly mobile and can move from plant to plant using the connections between the leaves and plastic mulch as bridges (Lopez et al, 2017). Moreover, they can be airborne, especially gravid females in search of prey or alternative food sources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low numbers of A. swirskii may also be explained by their high dispersal capacity. Amblyseius swirskii are highly mobile and can move from plant to plant using the connections between the leaves and plastic mulch as bridges (Lopez et al, 2017). Moreover, they can be airborne, especially gravid females in search of prey or alternative food sources.…”
Section: Discussionmentioning
confidence: 99%
“…Sweet alyssum was also attractive to predators such as Orius sp., and in many instances, syrphid flies (Syrphidae) were observed visiting alyssum flowers, but hardly any syrphids were collected by the sampling methods implemented. In contrast, high Amblyseius swirskii are highly mobile and can move from plant to plant using the connections between the leaves and plastic mulch as bridges (Lopez et al, 2017).…”
Section: Natural Enemiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Jung and Croft (2001a) reported a walking speed ranging from 0.1 to 0.4 mm/s for N. fallacis (2.7 h to move through 1 m). Raworth et al (1994) indicated than N. californicus would be able to walk 10 m within 1 h at 25 • C. Lopez et al (2017) studied the dispersal of A. swirskii to determine how it moved from bank plants to crops. They showed that canopy connectedness increased the dispersal of A. swirskii to the crops, whereas no impact of the prey Polyphagotarsonemus latus Banks was observed.…”
Section: Predatory Mite Dispersal Abilitiesmentioning
confidence: 99%
“…Within 24 h, A. swirskii dispersed within only 1 m from the banker plant. Canopy connectedness increased the number of predatory mites on the crop plants [27]. Spider mites are the most injurious pest in commercial plant nurseries.…”
Section: Dispersal From Banker Plants To Crops By Natural Enemiesmentioning
confidence: 99%